Vaccination of pregnant women against controlled respiratory tract infections - A. P. Cherdantsev; M. P. Kostinov; A. D. Shmitko; A. A. Cherdantseva (Журнал инфектологии, 2020)
The review provides information on the importance of immunoprophylaxis of epidemic controlled infections in pregnant women. It is shown that the most severe complications of pregnancy occur when women are infected with respiratory pathogens, especially influenza virus in the late stages of gestation. Newborns also have a high risk of fatal disorders and an infant mortality rate in cases of maternal influenza. Modern inactivated vaccines used in pregnant women in many countries since the second period of gestation have high safety and immunological efficacy for both women and the fetus. The issues of expediency, safety and effectiveness of vaccination of pregnant women against pneumococcus, Hemophilus type-b and pertussis infection are actively discussed, which reflects the evolution of understanding of the importance of this area of preventive medicine in obstetricpractice.